2,3,5,4'-tetrahydroxystilbene-2-O-b-D-glucoside triggers the pluripotent-like possibility of dental pulp stem cells by activating the JAK2/STAT3 axis: Preliminary observations - Yen-Wen Huang; Chi-Yu Lin; Yu-Tang Chin; Po-Jan Kuo; Yen Wu; I-Tsen Weng; Ting-Yi Chen; Hsin-Hui Wang; Haw-Ming Huang; Chao-Nan Hsiung; Sheng-Yang Lee (Elsevier, 2021)
Abstract Background/Purpose: Although 2,3,5,4'-Tetrahydroxystilbene-2-O-beta-glucoside (THSG) reportedly has anti-inflammatory properties, its role in inducing the dedifferentiation of human dental pulp stem cells (DPSC) into pluripotent-like stem cells remains to be determined. The purpose of this study is to evaluate the effects of THSG on the pluripotent-like possibility and mechanism of DPSC. Materials and methods: DPSCs were treated with THSG, and cell viability was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTS) assay. Real-time polymerase chain reaction was used to analyze the mRNA expression levels of pluripotency-associated genes and oncogenes and to detect telomerase activity in the cells. Embryoid body formation assay was conducted, and pluripotency-related proteins were identified using Western blotting. Data were analyzed using one-way analysis of variance. Results: Cell viability, telomerase activity, and embryoid body formation were enhanced in THSG-treated DPSCs. The mRNA expression levels of pluripotent-like genes (including Nanog homeobox [NANOG], SRY-box 2 [SOX2], and POU class 5 homeobox 1 [POU5F1/OCT4]) significantly increased after THSG treatment. The expression levels of pluripotency-related genes (Janus kinase-signal transducer 2 [JAK2] and signal transducer and activator of transcription 3 [STAT3]) increased, whereas those of oncogenes (Ras, SRC, HER2, and C-sis) decreased. Furthermore, the expression levels of the phosphorylated JAK2 and STAT3 proteins significantly increased after THSG treatment. Conclusion: THSG treatment may enhance the pluripotent-like possibility of DPSC through the JAK2/STAT3 axis. Hence, it may be used as an alternative cell-based therapeutic strategy in regenerative dentistry.